Prognostic Significance of Solitary Lymphnode Metastasis and Micrometastasis in Gastric Cancer - Mpallas, Konstantinos D.; Lagopoulos, Vasileios I.; Kamparoudis, Apostolos G. (Frontiers in Surgery, 2018)
Gastric cancer (GC) used to be one of the most common malignancies in the world and still is the second leading cause of malignancy-related death in the Far East. The most significant factors that were found to be associated with the clinical outcome in patients with M0 GC is tumor’s depth of invasion, the presence and the extend of lymphnode involvement, as well as the histological type according to Lauren (intestinal or diffuse). Although it is generally accepted that D2 gastrectomy is the procedure of choice to achieve adequate oncologic excision, there are quite many concerns for its use in patients with early gastric cancer (EGC), where No or N1 specimens are frequently reported. The last two decades, with the evolvement of cancer cell detection techniques, the attend of the medical community is focused on GC patients with solitary lymphnode metastasis (SLN) or micrometastasis (mM). There is a discussion whether SLN should be attributed as the “real” sentinel node (SN) and its projection on patients’ survival. The aim of this study is to review the recent literature and attempt to clarify the clinical significance of SLN in gastric cancer.